Biomass and phytoextraction potential of three ornamental shrub species tested over three years on a large-scale experimental site in Shanghai, China. Issue 1 (2nd January 2020) - Shang, Kankan; Hu, Yong hong; Vincent, Gilles; Labrecque, Michel
Abstract: Issues related to environmental degradation are of increasing concern worldwide. In urban Shanghai, many plant species used for ornamental purposes grow under harsh conditions yet show good resistance to pollution. Twelve shrub species were tested in a previous study to evaluate their capacity to tolerate and absorb inorganic contaminants. Among these, Hibiscus mutabilis and H. hamabo and Senna corymbosa, presented good performance and were tested over three growing seasons in a large experimental design (2000 m 2 ) where the soil was spiked with salts of Cu, Pb, or Zn. Each year of the study, all plants were cut and biomass was harvested and analyzed. Despite the relatively high concentration of metals in plots, no signs of toxicity were observed. Concentrations of metals in root tissues were generally much higher than those found in aerial parts. The bioconcentration factor values were generally very low, but the high biomass yield produced by H. mutabilis led to significant removal of Cu and Zn. No difference in the quantity of Pb extracted was found between species. As these plants respond well to coppicing, it may be possible to gradually eliminate contaminants from soils. Their use can also embellish the landscape while generating many other ecological services.